Influence of Four Dimensions of Environmental Management on Solid Waste Management, in the Ciudad Nueva District, Tacna, Peru - Moreno-Salazar-Calderón, Khiara Aliyah Bet (2025)
The objective of this research was to determine the influence of four dimensions of environmental management on solid waste management in the Ciudad Nueva District. These dimensions are classified into: environmental oversight, environmental governance, environmental education and environmental information. A sample of 390 families residing in the Ciudad Nueva District was considered, which were selected through simple random probabilistic sampling. The collection of primary source information was carried out, through the survey technique, during the months of July and August 2024. Two questionnaires, Likert scale type, were used: environmental management and solid waste management, with 18 and 22 items respectively. The results achieved demonstrate that solid waste management is influenced by the four dimensions of environmental management: environmental oversight, environmental governance, environmental education and environmental information, so by increasing the level of each of them, waste management is improved. solid waste.